Intra and interpersonal determinants for relapse in drug addicts - Ferreira, Aline Cristina Zerwes (2016)
A descriptive qualitative research conducted with 20 drug addicts during treatment at a Center of Psychosocial Attention for Alcohol and other Drugs, aimed to identify intra and interpersonal determinants of relapse perceived by the drug addict. The data were collected through semi-structured interviews, submitted to Content Analysis, and organized into categories following predictive determinants for relapse. The relapse occurred by intrapersonal determinants, as self-efficacy expressed by self-confidence in interrupting the drug consumption; the result expectation by anticipation of pleasurable drug effects; the motivation by the absence of volition to interrupt the consumption; coping with the difficulty to confront daily problems; negative and positive emotional states; and craving. Interpersonal determinants expressed by social support were related to the influence of thirds. The identification of these determinants during treatment to favor relapse prevention and effective rehabilitation.